Striatal morphology correlates with frontostriatal electrophysiological motor processing in Huntington's disease: an IMAGE‐HD study. Issue 12 (27th July 2016) - Turner, Lauren M.; Jakabek, David; Wilkes, Fiona A.; Croft, Rodney J.; Churchyard, Andrew; Walterfang, Mark; Velakoulis, Dennis; Looi, Jeffrey C. L.; Georgiou‐Karistianis, Nellie; Apthorp, Deborah
Abstract: Background: Huntington's disease (HD) causes progressive atrophy to the striatum, a critical node in frontostriatal circuitry. Maintenance of motor function is dependent on functional connectivity of these premotor, motor, and dorsolateral frontostriatal circuits, and structural integrity of the striatum itself. We aimed to investigate whether size and shape of the striatum as a measure of frontostriatal circuit structural integrity was correlated with functional frontostriatal electrophysiological neural premotor processing (contingent negative variation, CNV), to better understand motoric structure–function relationships in early HD. Methods: Magnetic resonance imaging (MRI) scans and electrophysiological (EEG) measures of premotor processing were obtained from a combined HD group (12 presymptomatic, 7 symptomatic). Manual segmentation of caudate and putamen was conducted with subsequent shape analysis. Separate correlational analyses (volume and shape) included covariates of age, gender, intracranial volume, and time between EEG and MRI. Results: Right caudate volume correlated with early CNV latency over frontocentral regions and late CNV frontally, whereas right caudate shape correlated with early CNV latency centrally. Left caudate volume correlated with early CNV latency over centroparietal regions and late CNV frontally. Right and left putamen volumes correlated with early CNV latency frontally, and right and left putamen shape/volume correlated with parietal CNV slope. Conclusions: Timing (latency) and pattern (slope) of frontostriatal circuit‐mediated premotor functional activation across scalp regions were correlated with abnormalities in structural integrity of the key frontostriatal circuit component, the striatum (size and shape). This was accompanied by normal reaction times, suggesting it may be undetected in regular tasks due to preserved motor "performance." Such differences in functional activation may reflect atrophy‐based frontostriatal circuitry despecialization and/or compensatory recruitment of additional brain regions. Abstract : Research on Huntington's disease (HD) suggests that presymptomatic individuals show no functional motor abnormalities despite significant and well‐established structural degeneration; however, our previous paper (Turner et al., PLoS One, 2015) identified aberrant premotor activation, which we suggest implicated frontostriatal network impairment. Here, we expand on our first study to demonstrate correlations between premotor activation and morphology of the striatum in a combined HD sample, suggesting that functional connectivity and motor compensation is dependent on structural integrity of such regions.